Independence is Sovereignty in the Philosophical Dimension - Yunus, Nur Rohim (BULETIN ADALAH, 2024)
This essay discusses the close relationship between independence and sovereignty of a state, as well as the challenges faced in the era of globalisation. The independence of a state does not only mean freedom from colonialism, but also includes the full right to regulate domestic affairs without external intervention. State sovereignty is the power to run the government, make policies, and maintain domestic stability. International recognition strengthens independence and autonomy, allowing the state to participate in the global system. However, globalisation creates challenges, where states often face international pressures that reduce the room for sovereignty. Therefore, states must develop strong institutional capacity and strengthen internal stability to maintain sovereignty. By strengthening the legal system and international relations, states can maintain their integrity and respond to increasingly complex global dynamics.